Spinel harzburgite–derived silicate melts forming sulfide-bearing orthopyroxenite in the lithosphere. Part 2: Sulfide compositions and their chalcophile and highly siderophile trace element signatures - Bénard, A. (Frontiers in Earth Science, 2022)
In the first article, we have reported petrological data for a new, glass-bearing orthopyroxenite vein cutting a sub-arc mantle xenolith from Kamchatka. As similar veins from the West Bismarck arc, this orthopyroxenite is sulfide-rich and formed by cooling of parental melts derived by partial melting of spinel harzburgite sources. Here I report new data for the abundances of major base metals and chalcophile and highly-siderophile trace elements in vein sulfides from the two localities. Kamchatka vein sulfides are all Cu-poor monosulfide solid solution (MSS). West Bismarck veins contain MSS and a ternary (Fe, Cu, Ni)S solid solution (‘xSS’), which ranges between MSS and intermediate solid solution (ISS) in composition. Sulfides follow Ni and Cu enrichment trends and have chondrite-normalized platinum-group element (PGE) patterns with elevated Pt and Pd relative to Os, Ir, Ru and Rh. Pt alloys are frequently associated with sulfides and vugs formed from hydrothermal fluids, where metallic Fe and wüstite were also identified. Vein sulfides, ranging from Fe-rich MSS (ca. 1050-1100°C) to xSS (≤850°C) through Ni-rich MSS, formed in a sulfide liquid line of descent under oxygen and sulfur fugacity conditions (fO2 and fS2) down to one log unit below the fayalite-magnetite-quartz and close to the Pt-PtS buffers, respectively. The Ni and Cu enrichment trends in MSS are consistent with cooling and fractionation of Ni-rich and Cu-poor sulfide liquids (original atomic metal/S~0.9), which will finally solidify as xSS or ISS. Chondrite-normalized Pt/Pd>1 in some of the sulfides is a signature of spinel harzburgite sources. Because it occurs at relatively low fS2, the crystallization sequence of these sulfide liquids is accompanied by the formation of abundant PGE alloys and other metallic phases. Melts derived from spinel harzburgite sources can be originally oxidized to carry up to 2600 ppm S (predominantly as S6+) and follow a sulfide-undersaturated evolution trend, until they are rapidly cooled to crystallize as orthopyroxenite dykes or sills. There, S6+-Fe2+ redox reactions with host rocks, together with the production of high-Mg# andesite derivatives with low S solubility and hydrothermal fluids at decreasing fO2 and fS2, will lead to the local precipitation of abundant sulfides and alloys.